Kelengkapan Ruang l^p pada Ruang Norm-n - Meriam, Meriam; Aris, Naimah; Nur, Muh. (Jurnal Matematika, Statistika dan Komputasi, 2018)
<img src="data:image/png;base64,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" alt="" width="451" height="52" />